Microhistory and Historical Anthropology - Nodl, Martin (Dějiny – teorie – kritika, 2024)
This article seeks to define the relationship between historical anthropology and three different levels of the conception of microhistory: 1) microhistory, the heroes of which are representatives of the lower strata of society, marginal or exceptional individuals; 2) microhistory of conflict; 3) "demographic" or "population" microhistory. On the basis of comparison of the original methodological starting points of Italian micro-historians with the microhistorical works of the 1980s and 90s, it emphasises the experimental character of this microhistorical research, considering the issue in the context of the work of historians who openly identified with micro-history, and looking in detail at the examples of Carlo Ginzburg and Emmanuel Le Roy Laduries. On the other hand, with reference to study of the relations between microhistory and prosopography it shows that a whole range of microhistorical approaches have deeper roots in the medievalist scholarship of the 1950s and 60s and that the novelty of the later decades consisted primarily in the posing of anthropological questions and emphasis on the sublateral strata of society, conceived not quantitatively by through exceptional individuals. The article takes a very critical view of the so-called "demographic" microhistory cultivated by the Göttingen School, and tries to show that it lacks and genetic kinship to the two other microhistorical approaches outlined and that here the only criterion of microhistoricity is the limitation of research to a very small local community and its family structures.